Efficient Wavelength-Tunable Gain-Switching and Gain-Switched Mode-Locking Operation of a Heavily Er3+-Doped ZBLAN Mid-Infrared Fiber Laser - Yanlong Shen; Yishan Wang; Kunpeng Luan; Hongwei Chen; Mengmeng Tao; Jinhai Si (IEEE Photonics Journal, 2017)
We report on an efficient wavelength-tunable gain-switched and gain-switched mode-locked Er3+-doped double-clad fiber laser with a linear cavity. Stable gain-switching and gain-switched mode-locking were achieved with slope efficiencies of 28.6% and 34.5% with respect to launched pump power, respectively. The gain-switched laser pulses were generated with a maximum average output power of around 110 mW, pulse width of 661.2 ns, and calculated peak power of ∼16.5 W at a repetition rate of 10 kHz. At the same repetition, the gain-switched mode-locked laser pulses were generated with a maximum average output power of around 514 mW, subpulse repetition rate of ∼30.7 MHz, and peak power of higher than 154 W at a repetition rate of 10 kHz when the wavelength was tuned to 2.78 μm. This is, to the best of our knowledge, the first demonstration of a gain-switched self-started mode-locked fiber laser near 3 μm.